Pengaruh Metode Eksperimen Terhadap Peningkatan Kemampuan Mengkomunikasikan dan Penguasaan Konsep Termokimia - I Wayan Agustika; Tasviri Efkar; Emmawaty Sofya (Universitas Lampung, 2018)
This study aims to describe the effect of the experimental method in increasing the learning activities and mastering students' concepts in temochemical material. This study used a quasi-experiment method with pretest-posttest control design. The population of this study was students of grade XI of science class High School in Bandar Lampung. Sampling uses cluster random sampling. In the experimental class using XI science 4 and class XI science 6 as a class control. The results showed that the experimental method had aneffect on increasing the students’ learning activities with a percentage of 79.97% and mastery of students concepts in the experimental class increases based on the average n-Gain score and the